PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. TELEKOMUNIKASI INDONESIA WILAYAH SUMATERA SELATA (WITEL SUMSEL) Tbk - Deasy Ariani; Marlina Widiyanti; Bambang Bemby Soebyakto; Mohamad Adam (The Manager Review, 2020)
The purpose of this study was to determine the effect of Transformational Leadership Style and Work Discipline on Employee Performance of PT. Telekomunikasi Indonesia, South Sumatra Region (Witel Sumsel) Tbk. The population in the study amounted to 103 employees with Non Probability Sampling. The analysis technique used by researchers was multiple linear regression analysis. The results of the analysis showed that there was an implication of a significant influence between transformational leadership style variables and work discipline that the attention of a manager made employees work enthusiasm used the test. In order to improve employee performance, it is recommended that managers and management continue to train employees to be more productive in the company to face challenges and focus on solving company problems. For future researchers, it is hoped that further researchers will develop unfinished variables such as motivation and corporate culture.